2006
DOI: 10.1007/s00606-006-0412-2
|View full text |Cite
|
Sign up to set email alerts
|

A phylogeographic study of the cosmopolitan genus Phragmites (Poaceae) based on AFLPs

Abstract: Within the genus Phragmites (Poaceae), the species P. australis (the common reed) is virtually cosmopolitan, and shows considerable variation in ploidy level and morphology. Genetic variation in Phragmites was studied using AFLPs, and analysed with parsimony and distance methods. Groups of P. australis strongly supported in the analyses include one that comprises all South American clones, a distinct group from the US Gulf Coast, and a group of E. Asian and Australian octoploids. Among the other species, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
159
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(168 citation statements)
references
References 38 publications
5
159
1
Order By: Relevance
“…4), that it is not unreasonable to hypothesize that there may be reproductive isolating mechanisms between them. Our results therefore support the recent contention of Lambertini et al (2006) that species status for the gulf coast and its related South American lineage should be considered. Previously, Saltonstall et al (2004) recommended referring to the gulf coast lineage as P. australis var.…”
Section: Discussionsupporting
confidence: 92%
“…4), that it is not unreasonable to hypothesize that there may be reproductive isolating mechanisms between them. Our results therefore support the recent contention of Lambertini et al (2006) that species status for the gulf coast and its related South American lineage should be considered. Previously, Saltonstall et al (2004) recommended referring to the gulf coast lineage as P. australis var.…”
Section: Discussionsupporting
confidence: 92%
“…The leaf characters resemble those of Phragmites mauritianus Kunth (Scholz and Böhling, 2000). Recent genetic studies have shown that the Gulf Coast clones are more related to P. mauritianus than to P. australis (Lambertini et al, 2006). Hence, it is not surprising that this clone differs significantly, particularly in morphological parameters.…”
Section: Effect Of Geographical Originmentioning
confidence: 94%
“…The large leaves were not caused by large cell sizes, as the length of guard cells did not deviate from that of the other clones. Genetic AFLP analyses have shown that the Israeli clone, even though it is tetraploid, is genetically closely related to the Australian group of octoploids (Lambertini et al, 2006). The Israeli clone therefore seems to resemble the Australian P. australis both genetically and in morphology.…”
Section: Effect Of Geographical Originmentioning
confidence: 99%
See 2 more Smart Citations